2017
DOI: 10.5937/psistra1701089s
|View full text |Cite
|
Sign up to set email alerts
|

Social factors outside of family and school related to student dropout

Abstract: The paper presents a systematisation of broader social factors affecting student dropout in Serbia from the framework of Bronfenbrenner's approach. Although recognised by authors and commonly related to community and education as a system, these factors are rarely investigated. Starting from our previous research into dropout, focused primarily on family and school, this study is aimed at investigating community and systemic factors. The data were compiled by semi-structured interviews with respondents from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This study represents a part of a comprehensive mixed-method research that addressed contextual and personal factors related to dropout (for more see Krstić, Videnović, Stepanović Ilić, Lazarević & Simić, 2015;Stepanović Ilić, Lazarević & Simić, 2017;Videnović & Lazarević, 2017). It builds on data collected through the qualitative part of that more comprehensive research, but focuses more deeply on the issues at the school level 3 .…”
Section: Research Topic and Objectivementioning
confidence: 99%
“…This study represents a part of a comprehensive mixed-method research that addressed contextual and personal factors related to dropout (for more see Krstić, Videnović, Stepanović Ilić, Lazarević & Simić, 2015;Stepanović Ilić, Lazarević & Simić, 2017;Videnović & Lazarević, 2017). It builds on data collected through the qualitative part of that more comprehensive research, but focuses more deeply on the issues at the school level 3 .…”
Section: Research Topic and Objectivementioning
confidence: 99%
“…One sociological survey (Cvejić et al, 2010) found that the dropout rate in rural areas was close to 45%. Systematising the dropout factors outside school and family from the ecological perspective, one recent investigation (Stepanović Ilić, Lazarević & Simić, 2017) named the following negative ecosystem influences connected to poor regions: lack of coordination between educational profiles and shortages on the job market; lack of career guidance in schools; parents going abroad to work, which leads to discontinued education of their children. The authors dealing with the characteristics of the educational system in Serbia often stress its unfavourable features associated with dropout.…”
Section: Systemic Factorsmentioning
confidence: 99%
“…In addition, Ilic and Simic (2017) suggest that efforts to reduce dropout rates should consider a comprehensive approach that addresses factors at multiple levels of the social ecology. This includes strengthening connections between schools, families, and local institutions, improving the quality of neighborhoods, and promoting cooperation and effective legislation at the macrosystem level.…”
mentioning
confidence: 99%